Synthesis of Pd–Ru solid-solution nanoparticles by pulsed plasma in liquid method. Issue 22 (1st April 2020) - Mashimo, Tsutomu; Tamura, Shota; Yamamoto, Kenta; Kelgenbaeva, Zhazgul; Ma, Weijan; Tokuda, Makoto; Koinuma, Michio; Isobe, Hiroshi; Yoshiasa, Akira
Abstract : We have synthesized solid-solution nanoparticles (Pd : Ru = 1 : 3, 1 : 1 and 3 : 1) in an immiscible Pd–Ru system by the pulsed plasma in liquid method using Pd–Ru mixture bulk electrodes. Abstract : We have synthesized solid-solution nanoparticles (Pd : Ru = 1 : 3, 1 : 1 and 3 : 1) in an immiscible Pd–Ru system by the pulsed plasma in liquid method using Pd–Ru mixture bulk electrodes. The particle sizes of the floated and sedimented samples were measured to be <10 and <20 nm, respectively, via high-resolution transmission electron microscopy (HR-TEM). The lattice parameters of nanoparticles followed the Vegard's law, and the energy-dispersive X-ray spectroscopy (EDX) results almost coincided with those obtained for the starting bulk mixtures. The solid-solution structures and local structure were confirmed via HR-TEM, X-ray photoelectron spectroscopy (XPS) and X-ray absorption fine structure spectroscopy (XAFS).